Bibliography of publications : Technical Department, Africa Region, July 1987 to April 1996 - Mohan, P.C (The World Bank, 1996)
This Bibliography of Publications of the Technical Department, Africa Region of the World Bank makes available a complete list of all formal and informal publications produced by the staff and consultants of the Africa Technical Department from July 1987 through April 1996. The publications cover the Technical Department's work in Africa in all sectors